Making and unmaking political subjectivities: Climate justice, activism, and care. Issue 4 (12th April 2020) - Bond, Sophie; Thomas, Amanda; Diprose, Gradon
Abstract : Much recent work on climate justice and activism focuses on the broader socio‐political economic contexts in which contestation occurs. These contestatory spaces in neoliberalised economies are frequently depoliticised through a variety of processes, strategies, practices, and actors. Recently this has been framed as the post‐political – whereby dissent is legitimised as "democratic" only when it does not challenge the status quo of business‐as‐usual. Most of the analysis and commentary on the post‐political has focused on policy or democratic decision‐making processes and conflict at relatively broad scales, rather than nuanced empirical case studies. In this paper we draw on an empirical case study to explore how processes of delegitimisation affect climate justice activists in emotional and personal ways. We argue that while the political subjectivities of climate justice activists are fragile achievements, a key aspect that sustains them is an ethic of care for humans and non‐humans, both near and more distant, who are affected by climate change. Fostering this ethic of care is one key way for climate activists to continue enacting responsibility for climate justice in a way that contests depoliticising and delegitimisation processes. Abstract : In this paper we draw on an empirical case study to explore how processes of delegitimisation affect climate justice activists in emotional and personal ways. We argue that while the political subjectivities of climate justice activists are fragile achievements, a key aspect that sustains them is an ethic of care for humans and non‐humans, both near and more distant, who are affected by climate change. Fostering this ethic of care is one key way for climate activists to continue enacting responsibility for climate justice in a way that contests depoliticising and delegitimisation processes.